What drives office rents? - Christian Bjørland; Marius Hagen (Norges Bank, 2019)
Banks have substantial exposures to commercial real estate (CRE). Rental prices are important for CRE companies' debt-service capacity, which in turn affects the risk of future bank losses. In this paper, we estimate error correction models (ECMs) to determine the main drivers of office rents in Oslo and to detect deviations in rents from their estimated long-run equilibrium. We find that employment and stock of offices are important explanatory variables. Moreover, our results show that rents have followed their estimated equilibrium closely and have re-adjusted quickly in periods of deviation.
hdl:11250/2653111
Keywords: C20; E30; R30; 330; Rental prices; commercial real estate; financial stability